Assessing wetland nitrogen removal and reed (Phragmites australis) nutrient responses for the selection of optimal harvest time. (15th February 2021) - Wang, Junli; Chen, Guifa; Fu, Zishi; Qiao, Hongxia; Liu, Fuxing
Abstract: Wetlands play an important role in reducing the impact of nitrogen pollution on natural aquatic environments. However, during the plant wilting period (winter) there will inevitably be a reduction in nitrogen removal from wetlands. Understanding optimum harvest time will allow the use of management practices to balance the trade-off between nitrogen removal and the sustainability of wetlands. In this study, we investigated wetland nitrogen removal and reed ( Phragmites australis ) nutrient responses for two years [first year: influent total nitrogen (TN) 17.6–34.7 mg L −1 ; second year: influent TN 3.2–10.0 mg L −1 ] to identify the optimal harvest time: before wilting, mid-wilting, or late wilting. Harvesting decreased wetland nitrogen removal in both years, with later harvest time producing a smaller decrease in TN and ammonium-nitrogen (NH4 + –N) removal. In addition to harvest before wilting, aboveground reed harvest at mid-wilting harvested more nutrients [carbon (C) 7.9%, nitrogen (N) 46.6% and phosphorus (P) 43.6%] in the first year, while harvest at late wilting harvested more nutrients (C 4.9%, N 7.8% and P 24.1%) in the second year, although this was not statistically significant. The late wilting harvest caused fewer disturbances to root stoichiometric homeostasis in the first year, while mid-wilting harvest promoted root nutrient availability in the second year. In addition, redundancy analysis (RDA) showed that root stoichiometry was interrelated with wetland nitrogen removal. Our results suggest that optimal harvest time was late wilting on the basis of wetland nitrogen removal, or either mid- or late wilting according to reed nutrient response to influent nitrogen concentration in some years. Our results provide crucial information for winter wetlands management. Highlights: Later harvest times had less impact on wetland TN and NH4 + –N removal. Mid- or late-wilting harvest should be selected according to reed nutrient response. Root stoichiometric characteristics were related to wetland nitrogen removal.